LANGUANGE CHANGE IN ORAL CULTURE OF MINANGKABAU SOCIETY: A DIACHRONIC STUDY (PERUBAHAN BAHASA DALAM BUDAYA LISAN MASYARAKAT MINANGKABAU: SEBUAH STUDI DIAKRONIS ) - Silvia Djonnaidi (Universitas PGRI Sumatera Barat, 2020)
This article shows the language change which occurs in the oral culture of Minangkabau society. The oral culture which is analyzed is the vocabularies which are used in the product of Minangkabau pop-culture which occurs in Minangkabau songs during the era of 1950-s and 1990-s. Minang’s song is used as the object of the study becausethis songs have a bigger tendency of having language change in its lyrics.It happens since songs are the product of oral folklore in Minangkabau society always follow the current development. The method in collecting the data is non participant observational method with the note-taking technique. The method in analyzing the data is intralingual equivalent method. In order to find out languange retention and inovation, a top-down approach is also used in analyzing the data. The result of the analysis is presented in formal and informal ways. The result of languange analysis shows that there are some shift in meaning which happens lexically and semantically from both of this era. The languange change is shown through the changing in some vocabularies which had an innovation in meaning during the times.